Upaya Meningkatkan Pemahaman tentang Pembagian Waris dalam Hukum Islam pada Masyarakat Desa Margajaya Kabupaten Ciamis - Nurcholis, Muhamad erliana; Sulaeman, Amon; Nasirudin, Dadi (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2022)
The law of inheritance, which remains prevalent and continues to exist within society, governs the distribution of inheritance in Indonesian society. This distribution is primarily guided by Islamic law and customary practices. The reason for this is that the Indonesian population consists mostly of Muslims belonging to different tribes, resulting in a highly diversified inheritance distribution that is influenced by the family system they follow. This action was undertaken due to the little awareness of inheritance distribution in the Margajaya Village area, located in the Pamarican District. The division of inheritance in this region occurs in two distinct forms: the distribution of inheritance governed by Islamic law and the distribution of inheritance governed by customary law. In the event of a dispute arising from the allocation of the inheritance, a process of reconciliation will be undertaken. According to several experts, islah is deemed permissible under Islamic law, as inheritance falls under the domain of muamalah, which is subject to human discretion, as long as there is no disagreement in this matter. In this scenario, the distribution of inheritance is determined through amicable agreement and is based on their mutual consensus and personal advantage.